'Take Care Earth': Death and Re-birth as an Eco-critical Paradigm in Doris Lessing's Briefing for a Descent into Hell. Issue 1 (2nd January 2021) - Almaeen, Mona
ABSTRACT: This paper approaches spirituality as an eco-critical paradigm in Doris Lessing's Briefing for a Descent into Hell . Lessing's unorthodox and extended literary production, which was crowned with a Nobel Prize in Literature in 2007, is considered by many critics controversial due to Lessing's stand on colonialism, as well as her critique of both communism and feminism. This paper engages with the manner in which Lessing depicts modern patterns of individuality as ecologically destructive because she sees in them an accentuation of the material and selfish aspects of modern civilisation. For her, spirituality offers an alternative view of individuality based on a cosmological oneness, or a unification of the inner and cosmological spaces via the mystical experience of death and re-birth. Utilising a combination of contextual and textual approaches, this paper examines Lessing's depiction of the intersection of the mystical and the profane and the impact of this intersection in recreating this alternative individual identity.